Type studies on frullania subgenus meteoriopsis (hepaticae). ii. on f. apollinarii and f. paranensis (2004)
As a result of a redefinition of subgenus Meteoriopsis and the study of type material,Frullania apollinarii Steph. is transferred from this subgenus to subgenusThyopsiella and F. paranensis to subgenus Chonanthelia.